Letter to the editor of Heliyon re: Bioinformatics-based prediction and screening of immunogenic epitopes of Toxoplasma gondii rhoptry proteins 7, 21 and 22 as candidate vaccine target - Ayub, Fariha; Ahmed, Haroon; Sohail, Tehreem; Shahzad, Khurram; Celik, Figen; Wang, Xu; Cao, Jianping (Cell Press, 2024)
[Abstract Not Available]
Keywords: B-Cell Epitopes; Identification; Infection; Cattle